Rancang Bangun Sistem Informasi Kepegawaian (Studi Kasus : PT Dekatama Centra) - Julian Chandra Wibawa; Fany Julianto (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Human Resources (HR) are element or very important asset in the company. Human Resource Management is a process to deal with the issues on the scope of employees, managers and other workers to be able to support the activities to achieve the predetermined goals. The development of science and technology at this time brings a lot of benefits and services, for example, computer helps to perform data processing in a systematic, statistical data processing and others. Therefore, this research has built HRM aplication using waterfall method. The data collection uses interview and observation methods. This HRM application describes the interaction between user and application system, which each user has different access rights tailored to job functions. In addition, this application can be attributed to the Hardware Finger Print originating from a different place or location.The softwares used to build the systems were HTML, PHP, Javascript, css, and MySQL while the blackbox method was used to test the information system. The HRM application is expected to help the processing of employee data, so that the HRD division works more effectively and efficiently. HRM application can display employee data, employee history, length of employment, labor contracts, attendance data, payroll data, salary recapitulation, receipt of salary, employee benefits, salary increment, leave application, chunks of cash receipt and setting work hours.Â Keywordsâ€” HRM, Fingerprint, Salary.